Linguistic creativity in social media (via the example of Facebook pages of coffee shops) - Kujawiak, Aleksandra (Linguistic creativity in marketing, 2022)
The article contains an analysis of creative linguistic and stylistic means used in online advertising. The research material consists of posts published on the Facebook fan pages of three coffee shop chains: Costa Coffee Poland, Green Caffè Nero and So! Coffee, in the period 2019-2020. The following groups of means are discussed in the text: metaphors (including: synesthetic metaphors, hyperbolas and personifications), modifications of phraseologisms and proverbs, intertextual references, examples of using the ambiguity of words (polysemy) and their sonic similarity (homonymy), and graphic means.